Ratio of Liquidity, Profitability and Activity to the Remaining Profit of Cooperatives in Sidoarjo Regency: Rasio Likuiditas, Profitabilitas dan Aktivitas terhadap Besarnya Sisa Hasil Usaha Koperasi di Kabupaten Sidoarjo - Fitriyanti, Erika; Nurasik, Nurasik (Indonesian Journal of Innovation Studies, 2023)
This research aims analyze the effect of liquidity ratio, profitability, and activity on the amount of the remaining operating results of cooperatives in Sidoarjo Regency in 2019-2020. This research uses secondary data. This research method uses quantitative, the population in this study is 720 active cooperatives in Sidoarjo Regency and 21 cooperatives during 2019-2020 period which are used as research samples. The sample selection in this research was taken with the type of probability sampling with a simple random sampling method. Data collection techniques using documentation. The data analysis technique used SPSS version 26. The results in this research indicate that the liquidity ratio partially affects the amount of the remaining operating results of cooperatives, the profitability ratio partially has no effect on the amount of the remaining operating results of cooperatives, and the activity ratio partially has no effect on the amount of the remaining results of cooperative operations.